A container for batteries and energy storage system
Patent Information
- Application Number
- CN202521491791.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2035-07-16
AI Technical Summary
但是,这种结构会导致集装箱内部的空间体积减少,进而降低了集装箱中电池的能量密度
[0027]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN224830521U_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more particularly to a battery container and energy storage system. Background Technology
[0002] As a standardized loading unit for logistics and transportation, the core function of a shipping container is to provide a safe and stable storage environment for goods. When transporting batteries in containers, the containers need to have good fire resistance and thermal insulation properties to maintain the chemical stability of the batteries. In related technologies, containers generally use a multi-layered rock wool board structure to achieve their fire resistance and thermal insulation effect. However, this structure reduces the internal volume of the container, thereby reducing the energy density of the batteries inside. Summary of the Invention
[0003] In view of this, this application provides a battery container and energy storage system, which can improve the internal space volume of the container while giving it good fire resistance, heat insulation and thermal insulation performance, thereby increasing the energy density of the battery in the container.
[0004] The first aspect of this application provides a battery container, which includes a container panel that surrounds a cavity. The container panel includes a base plate, an insulating coating, and a fire-resistant coating. The insulating coating is disposed on the side of the base plate away from the cavity, and the fire-resistant coating is disposed on the side opposite to the insulating coating, with the fire-resistant coating facing the cavity.
[0005] In the technical solution of this application embodiment, by placing the thermal insulation coating on the side of the substrate away from the accommodating cavity and placing the fire-resistant coating on the side opposite to the thermal insulation coating, with the fire-resistant coating facing the accommodating cavity, the risk of heat transfer from the external environment to the container interior can be reduced, and heat and fire sources can be effectively prevented from spreading outward, thus playing a role in fire resistance and heat insulation. Applying this container panel to a container allows the entire container to withstand prolonged high temperatures and flame impacts, thereby improving the container's fire resistance and heat insulation performance and maintaining a stable temperature environment for battery storage. Compared to traditional multi-layer rock wool board structures, this application, by coating the inner surface (i.e., the side near the accommodating cavity) and outer surface (i.e., the side away from the accommodating cavity) of the substrate with a fire-resistant coating and a thermal insulation coating respectively, enables the container to have better fire resistance, heat insulation, and heat insulation performance while also increasing the internal space volume of the container, thereby increasing the energy density of the batteries within the container.
[0006] In any embodiment, the thickness of the thermal insulation coating is 200 μm to 3 mm. By adjusting the thickness of the thermal insulation coating to the above range, both the thermal insulation performance and cost of the thermal insulation coating can be balanced.
[0007] In any embodiment, the hemispherical emissivity of the thermal insulation coating in the range of 200 μm to 3 mm is 85% to 99%. By adjusting the hemispherical emissivity of the thermal insulation coating in the range of 200 μm to 3 mm within the above range, more infrared radiation energy can be reflected rather than absorbed or conducted, effectively reducing heat transfer efficiency and thus improving the overall thermal insulation effect of the thermal insulation coating.
[0008] In any embodiment, the thermal conductivity of the insulation coating is 0.002 W / (m·K) to 0.05 W / (m·K). By adjusting the thermal conductivity of the insulation coating to the above range, the risk of heat transfer from the external environment to the interior of the container can be reduced, thereby maintaining a stable temperature in the battery storage environment.
[0009] In any embodiment, the insulation coating comprises at least one of acrylic acid, polyurethane, fluorocarbon, and silicone. Acrylic acid has good adhesion and weather resistance, effectively reducing the impact of the external environment on the internal temperature of the container. Polyurethane has good abrasion resistance and flexibility, which can improve the overall strength and impact resistance of the insulation coating. Fluorocarbon has good corrosion resistance, which can improve the corrosion resistance and chemical stability of the insulation coating. Silicone has good high-temperature resistance, which can improve the insulation performance of the insulation coating.
[0010] In any embodiment, the thermal insulation coating further includes hollow microspheres. The interior of the hollow microspheres is a cavity, and the gas within the cavity has a low thermal conductivity, effectively blocking heat conduction paths and reducing the thermal conductivity of the thermal insulation coating. The hollow microspheres also allow for the continuous refraction and reflection of mid- and far-infrared waves, resulting in excellent radiative thermal insulation performance. Furthermore, the hollow structure of the microspheres deforms under external forces (such as friction or impact), effectively absorbing and dispersing stress, reducing localized stress concentration, and thereby improving the wear resistance and stone impact resistance of the thermal insulation coating.
[0011] In any embodiment, the particle size of the hollow microspheres is 1 μm to 100 μm. By controlling the particle size of the hollow microspheres to be within the above range, it is beneficial to reduce the thermal conductivity of the insulation coating and at the same time reduce the overall weight of the insulation coating.
[0012] In any embodiment, the pore size of the hollow microspheres is 0.5 μm to 90 μm. By controlling the pore size of the hollow microspheres within the above range, it is beneficial to reduce the thermal conductivity of the insulating coating while maintaining a certain mechanical strength.
[0013] In any embodiment, the hollow microspheres include at least one of hollow ceramic microspheres, hollow alumina microspheres, hollow carbon microspheres, hollow polystyrene microspheres, and hollow polyimide microspheres. The above-mentioned types of hollow microspheres have low thermal conductivity and are structurally stable at high temperatures. Applying them to thermal insulation coatings can effectively reduce the thermal conductivity of the coatings and improve their structural stability at high temperatures.
[0014] In any embodiment, the insulating coating further includes aerogel. Aerogel has a porous structure, and the movement of gas molecules within the pores is restricted, which can significantly reduce heat conduction, thereby improving the thermal insulation effect of the insulating coating. The porous structure of aerogel allows it to absorb a large amount of energy upon impact through pore compression, significantly buffering the destructive force of high-speed impacts such as stone chips, thus improving the stone chip resistance of the insulating coating. In addition, aerogel has a low density, and its application in the insulating coating can reduce the weight of the insulating coating.
[0015] In any embodiment, the aerogel includes at least one of silica aerogel, carbon aerogel, alumina aerogel, zirconia aerogel, polymethyl methacrylate aerogel, and polyimide aerogel. Silica aerogel, polymethyl methacrylate aerogel, and polyimide aerogel have low thermal conductivity coefficients, and their application in thermal insulation coatings can reduce heat conduction; carbon aerogel, alumina aerogel, and zirconia aerogel have good high-temperature resistance properties, and their application in thermal insulation coatings can improve the high-temperature resistance properties of the thermal insulation coating.
[0016] In any embodiment, the thickness of the refractory coating is 1.5 mm to 20 mm. By adjusting the thickness of the refractory coating to the above range, both the refractory performance and cost of the refractory coating can be balanced.
[0017] In any embodiment, the refractory coating includes at least one of the following: a copolymer of epoxy and amine materials, a copolymer of hydroxyl polyurethane and isocyanate, a copolymer of acrylic acid and isocyanate, and polyurea. These materials belong to the category of two-component cross-linked curing materials. During curing, these materials undergo a chemical reaction to generate a highly cross-linked three-dimensional network structure. This structure allows the refractory coating to possess both fire-resistant and heat-insulating properties and higher mechanical strength, thereby improving its wear resistance. Some components in the two-component cross-linked curing material contain polar groups. These polar groups can form chemical bonds with oxides or treatment layers on the substrate surface, thereby enhancing interfacial bonding and improving adhesion to the substrate. Furthermore, the three-dimensional network structure is not easily decomposed at high temperatures, maintaining the structural integrity of the material and reducing the risk of decreased adhesion due to high-temperature softening.
[0018] In any embodiment, the refractory coating further includes at least one of ammonium phosphate compounds and their polymers, amine compounds and their derivatives, and polyol polymers. Ammonium phosphate compounds and their polymers can decompose at high temperatures, producing phosphoric acid and ammonia, which can effectively reduce the combustion rate and inhibit flame spread. Ammonium phosphate compounds and their polymers can also form inorganic compounds such as titanium pyrophosphate with inorganic fillers, releasing water vapor and ammonia, which can also reduce the combustion rate. Furthermore, the decomposition product phosphoric acid of ammonium phosphate compounds and their polymers can promote carbonization of polyol polymers and release water molecules for cooling. Amine compounds and their derivatives can decompose at high temperatures to generate nitrogen, carbon dioxide, and water vapor, which can effectively reduce the combustion rate. Polyol polymers can form a carbonaceous layer at high temperatures; this carbonaceous layer not only isolates oxygen but also absorbs heat, thereby slowing down the combustion process.
[0019] In any embodiment, the thermal conductivity of the refractory coating before expansion is 0.2 W / (m·K) to 0.4 W / (m·K). By adjusting the thermal conductivity of the refractory coating before expansion to the above range, the refractory coating can prevent the rapid spread of heat even in the unexpanded state, thereby achieving effective fire resistance and heat insulation effects even before expansion.
[0020] In any embodiment, a rock wool board is further disposed between the fire-resistant coating and the substrate. The use of the rock wool board further enhances the thermal insulation performance of the enclosure panel. The rock wool board not only effectively reduces heat transfer but also acts as a buffer and delays the spread of fire in the event of a fire, thus protecting the substrate from high-temperature damage. This structural design gives the enclosure panel greater stability and safety in high-temperature environments. The rock wool board serves as the bottom thermal insulation barrier, and the fire-resistant coating as the surface flame-retardant barrier, forming a dual protection of "physical thermal insulation and chemical flame retardancy," thereby effectively improving the fire resistance and thermal insulation effect of the enclosure panel.
[0021] In any implementation, the thickness of the rock wool board is less than or equal to 20 mm. By adjusting the thickness of the rock wool board to the above range, both the thermal insulation performance and internal volume of the container can be balanced. Rock wool boards with a thickness of less than or equal to 20 mm have a minimal impact on the internal space volume of the container, and consequently, a minimal impact on the energy density of the batteries inside the container.
[0022] In any embodiment, the thickness of the substrate is 1 mm to 3 mm. By adjusting the thickness of the substrate to the above range, both the mechanical properties and cost of the substrate can be balanced.
[0023] In any embodiment, the substrate includes a metal substrate. The metal substrate maintains high strength at high temperatures, enabling the container to maintain its overall structural integrity during a fire. Furthermore, the high thermal conductivity of the metal substrate rapidly dissipates heat, preventing localized overheating and delaying flame penetration time, thereby increasing the container's fire resistance.
[0024] In any embodiment, the metal substrate includes at least one of aluminum alloy, galvanized steel, stainless steel, and carbon steel. The aforementioned types of metal substrates can maintain high strength at high temperatures, enabling the container to maintain the integrity of its overall structure during a fire.
[0025] In any embodiment, the metal substrate comprises cold-formed thin-walled steel. Cold-formed thin-walled steel is prepared by a cold-forming process, and it has high strength and light weight. When applied to containers, it can improve the strength of the container and reduce the overall weight of the container.
[0026] A second aspect of this application provides an energy storage system comprising the aforementioned battery container and a battery, the battery being disposed within the accommodating cavity. In embodiments of this application, the energy storage system possesses at least the same advantages as the battery container of the first aspect.
[0027] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of a box panel provided in an embodiment of this application.
[0029] Figure 2 This is a schematic diagram of the structure of some of the box panels provided in the embodiments of this application.
[0030] Figure 3 This is another structural schematic diagram of the box panel provided in the embodiment of this application.
[0031] Explanation of key figure labels:
[0032] 1000 Box panel, 100 Substrate, 200 Fire-resistant coating, 300 Thermal insulation coating, 310 Hollow microspheres and aerogel, 400 Rock wool board, 500 Heat transfer path. Detailed Implementation
[0033] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery container and energy storage system of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0034] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0036] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0037] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0038] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0039] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0040] In related technologies, shipping containers commonly employ a multi-layered rock wool board structure to achieve their fire-resistant, heat-insulating, and thermal-insulating effects. However, this structure involves relatively thick rock wool boards, which reduces the internal space volume of the container and consequently lowers the energy density of the batteries within it.
[0041] To resolve the above technical issues, please refer to Figure 1 , Figure 1 This is a schematic diagram of a container panel provided in an embodiment of this application. The battery container provided in this application includes a container panel 1000, which encloses a receiving cavity. The container panel 1000 includes a base plate 100, a thermal insulation coating 300, and a fire-resistant coating 200. The thermal insulation coating 300 is disposed on the side of the base plate 100 away from the receiving cavity. The fire-resistant coating 200 is disposed on the side opposite to the thermal insulation coating 300, facing the receiving cavity.
[0042] In the technical solution of this application embodiment, by setting the thermal insulation coating 300 on the side of the substrate 100 away from the accommodating cavity and setting the fire-resistant coating 200 on the side opposite to the thermal insulation coating 300, with the fire-resistant coating 200 facing the accommodating cavity, the risk of heat transfer from the external environment to the container interior can be reduced, and heat and fire sources can be effectively prevented from spreading outward, thus playing a role in fire resistance and heat insulation. Applying this container panel 1000 to a container allows the entire container to withstand long-term high temperatures and flame impacts, thereby improving the fire resistance and heat insulation performance of the container and maintaining a stable temperature environment for battery storage. Compared with the traditional multi-layer rock wool board structure, this application, by coating the inner surface (i.e., the side near the accommodating cavity) and outer surface (i.e., the side away from the accommodating cavity) of the substrate 100 with the fire-resistant coating 200 and the thermal insulation coating 300 respectively, enables the container to have better fire resistance, heat insulation, and heat insulation performance while also increasing the internal space volume of the container, thereby increasing the energy density of the batteries in the container.
[0043] In any embodiment, the thickness of the thermal insulation coating 300 is 200μm to 3mm. By adjusting the thickness of the thermal insulation coating 300 to the above range, both the thermal insulation performance and cost of the thermal insulation coating 300 can be considered. Specifically, the thickness of the thermal insulation coating 300 can be 200μm, 500μm, 1mm, 2mm, 3mm, or any range of two of the above values, such as 200μm to 500μm, 500μm to 1mm, 1mm to 2mm, 2mm to 3mm, etc.
[0044] In any embodiment, the hemispherical emissivity of the thermal insulation coating 300 in the range of 200 μm to 3 mm is 85% to 99%. By adjusting the hemispherical emissivity of the thermal insulation coating 300 in the range of 200 μm to 3 mm to the above range, more infrared radiation energy can be reflected rather than absorbed or conducted, effectively reducing heat transfer efficiency and thus improving the overall thermal insulation effect of the thermal insulation coating 300. Specifically, the hemispherical emissivity of the thermal insulation coating 300 in the range of 200 μm to 3 mm is 85%, 88%, 92%, 96%, 99%, etc., or a range consisting of any two of the above values, such as 85% to 88%, 88% to 92%, 92% to 96%, 96% to 99%, etc.
[0045] In any embodiment, the thermal conductivity of the insulating coating 300 is 0.002 W / (m·K) to 0.05 W / (m·K). By adjusting the thermal conductivity of the insulating coating 300 to the above range, the risk of heat transfer from the external environment to the interior of the container can be reduced, thereby maintaining a stable temperature in the battery storage environment. The thermal conductivity of the insulation coating 300 is 0.002 W / (m·K), 0.01 W / (m·K), 0.02 W / (m·K), 0.03 W / (m·K), 0.04 W / (m·K), 0.05 W / (m·K), or a range of any two of the above values, such as 0.002 W / (m·K)~0.01 W / (m·K), 0.01 W / (m·K)~0.02 W / (m·K), 0.02 W / (m·K)~0.03 W / (m·K), 0.03 W / (m·K)~0.04 W / (m·K), 0.04 W / (m·K)~0.05 W / (m·K), etc.
[0046] In any embodiment, the thermal insulation coating 300 comprises at least one of acrylic acid, polyurethane, fluorocarbon, and silicone. Acrylic acid has good adhesion and weather resistance, effectively reducing the impact of the external environment on the internal temperature of the container. Polyurethane has good abrasion resistance and flexibility, which can improve the overall strength and impact resistance of the thermal insulation coating 300. Fluorocarbon has good corrosion resistance, which can improve the corrosion resistance and chemical stability of the thermal insulation coating 300. Silicone has good high-temperature resistance, which can improve the thermal insulation performance of the thermal insulation coating 300.
[0047] In any embodiment, the thermal insulation coating 300 further includes hollow microspheres. The interior of the hollow microspheres is a cavity, and the gas within the cavity has a low thermal conductivity, effectively blocking heat conduction paths and reducing the thermal conductivity of the thermal insulation coating 300. The hollow microspheres also allow for continuous refraction and reflection of mid- and far-infrared waves, resulting in excellent radiative thermal insulation performance. Furthermore, the hollow structure of the microspheres deforms under external forces (such as friction or impact), effectively absorbing and dispersing stress, reducing localized stress concentration, thereby improving the wear resistance and stone impact resistance of the thermal insulation coating 300.
[0048] In any embodiment, the particle size of the hollow microspheres is 1 μm to 100 μm. By controlling the particle size of the hollow microspheres to be within the above range, it is beneficial to reduce the thermal conductivity of the thermal insulation coating 300 and at the same time reduce the overall weight of the thermal insulation coating 300. The particle sizes of the hollow microspheres are 1 μm, 10 μm, 40 μm, 70 μm, 100 μm, etc., or any range of two of the above values, such as 1 μm to 10 μm, 10 μm to 40 μm, 40 μm to 70 μm, 70 μm to 100 μm, etc.
[0049] In any embodiment, the pore size of the hollow microspheres is 0.5 μm to 90 μm. By adjusting the pore size of the hollow microspheres to the above range, it is beneficial to reduce the thermal conductivity of the thermal insulation coating 300 while maintaining a certain mechanical strength. Specifically, the pore sizes of the hollow microspheres are 0.5 μm, 10 μm, 40 μm, 70 μm, 90 μm, etc., or any range of two of the above values, such as 0.5 μm to 10 μm, 10 μm to 40 μm, 40 μm to 70 μm, 70 μm to 90 μm, etc.
[0050] In any embodiment, the density of the hollow microspheres is 0.1 g / cm³. 3 ~1.0g / cm 3 By adjusting the density of the hollow microspheres to the aforementioned range, it is beneficial to reduce the overall weight of the thermal insulation coating 300 while maintaining a certain level of mechanical strength. Specifically, the density of the hollow microspheres is 0.1 g / cm³. 3 0.4g / cm 3 0.7g / cm3 1.0g / cm 3 =, etc., or a range of values consisting of any two of the above values, for example, 0.1 g / cm 3 ~0.4g / cm 3 0.4g / cm 3 ~0.7g / cm 3 0.7g / cm 3 ~1.0g / cm 3 wait.
[0051] In any embodiment, the hollow microspheres include at least one of hollow ceramic microspheres, hollow alumina microspheres, hollow carbon microspheres, hollow polystyrene microspheres, and hollow polyimide microspheres. The above-mentioned types of hollow microspheres have low thermal conductivity and are structurally stable at high temperatures. Applying them to the thermal insulation coating 300 can effectively reduce the thermal conductivity of the thermal insulation coating 300 and improve its structural stability at high temperatures.
[0052] In any embodiment, the thermal insulation coating 300 further includes aerogel. The aerogel has a porous structure, restricting the movement of gas molecules within its pores, which significantly reduces heat conduction, thereby improving the thermal insulation effect of the thermal insulation coating 300. The porous structure of the aerogel allows it to absorb a large amount of energy upon impact through pore compression, significantly buffering the destructive force of high-speed impacts such as stone chips, thus improving the stone chip resistance of the thermal insulation coating 300. Furthermore, the low density of the aerogel allows for a reduction in the weight of the thermal insulation coating 300.
[0053] In any implementation, please refer to Figure 2 , Figure 2 This is a schematic diagram of the structure of a portion of the enclosure panel 1000 provided in an embodiment of this application. The thermal insulation coating 300 includes hollow microspheres and aerogel 310. The hollow microspheres reflect some of the heat radiation, while the aerogel blocks some of the heat conduction. Only a small amount of heat propagates along the heat transfer path 500, and the two work together to reduce heat transfer efficiency. By combining hollow microspheres and aerogel 310, the thermal insulation coating 300 achieves a combination of lightweight and low thermal conductivity.
[0054] In any embodiment, the aerogel includes at least one of silica aerogel, carbon aerogel, alumina aerogel, zirconia aerogel, polymethyl methacrylate aerogel, and polyimide aerogel. Silica aerogel, polymethyl methacrylate aerogel, and polyimide aerogel have low thermal conductivity coefficients, and their application in the thermal insulation coating 300 can reduce heat conduction; carbon aerogel, alumina aerogel, and zirconia aerogel have good high-temperature resistance properties, and their application in the thermal insulation coating 300 can improve the high-temperature resistance properties of the thermal insulation coating 300.
[0055] In any embodiment, the thermal insulation coating 300 further includes at least one of nano-alumina, nano-magnesium oxide, nano-porous silica, and three-dimensional porous ceramics. Applying the above materials to the thermal insulation coating 300 can improve the hardness, wear resistance, and impact resistance of the thermal insulation coating 300.
[0056] In any embodiment, the thickness of the refractory coating 200 is 1.5 mm to 20 mm. By adjusting the thickness of the refractory coating 200 to the above range, both the fire resistance performance and cost of the refractory coating 200 can be considered. Specifically, the thickness of the refractory coating 200 is 1.5 mm, 5 mm, 10 mm, 16 mm, 20 mm, etc., or a range consisting of any two of the above values, such as 1.5 mm to 5 mm, 5 mm to 10 mm, 10 mm to 16 mm, 16 mm to 20 mm, etc.
[0057] In any embodiment, the refractory coating 200 includes at least one of the following: a copolymer of epoxy and amine materials, a copolymer of hydroxyl polyurethane and isocyanate, a copolymer of acrylic acid and isocyanate, and polyurea. These materials are two-component cross-linked curing materials. During curing, these materials undergo a chemical reaction to generate a highly cross-linked three-dimensional network structure. This structure allows the refractory coating 200 to possess both fire-resistant and heat-insulating properties and higher mechanical strength, thereby improving its wear resistance. Some components in the two-component cross-linked curing material contain polar groups. These polar groups can form chemical bonds with oxides or treatment layers on the substrate surface, thereby enhancing interfacial bonding and improving adhesion to the substrate. Furthermore, the three-dimensional network structure is not easily decomposed at high temperatures, maintaining the structural integrity of the material and reducing the risk of decreased adhesion due to high-temperature softening.
[0058] In any embodiment, the refractory coating 200 further includes at least one of ammonium phosphate compounds and their polymers, amine compounds and their derivatives, and polyol polymers. Ammonium phosphate compounds and their polymers can decompose at high temperatures, producing phosphoric acid and ammonia, which can effectively reduce the combustion rate and inhibit flame spread. Ammonium phosphate compounds and their polymers can also form inorganic compounds such as titanium pyrophosphate with inorganic fillers, releasing water vapor and ammonia, which can also reduce the combustion rate. Furthermore, the decomposition product phosphoric acid of ammonium phosphate compounds and their polymers can promote carbonization of polyol polymers and release water molecules for cooling. Amine compounds and their derivatives can decompose at high temperatures to generate nitrogen, carbon dioxide, and water vapor, which can effectively reduce the combustion rate. Polyol polymers can form a carbonaceous layer at high temperatures; this carbonaceous layer not only isolates oxygen but also absorbs heat, thereby slowing down the combustion process.
[0059] In one specific embodiment, ammonium phosphate compounds and their polymers include ammonium polyphosphate, amine compounds and their derivatives include melamine, and polyol polymers include pentaerythritol. As in chemical reaction (1), ammonium polyphosphate decomposes at high temperatures to generate phosphoric acid and ammonia, which effectively reduce the combustion rate and inhibit flame spread. As in chemical reaction (2), ammonium polyphosphate can also react with the inorganic filler titanium dioxide to form the inorganic compound titanium pyrophosphate, releasing water vapor and ammonia, which also reduce the combustion rate. Furthermore, the decomposition product of ammonium polyphosphate, phosphoric acid, promotes the carbonization of pentaerythritol and releases water molecules for cooling. As in chemical reaction (3), pentaerythritol and phosphoric acid react to generate water and a carbonaceous layer, which not only isolates oxygen but also absorbs heat, thereby slowing down the combustion process. As in chemical reaction (4), melamine decomposes at high temperatures to generate nitrogen, carbon dioxide, and water vapor, which effectively reduce the combustion rate.
[0060]
[0061] In any embodiment, the refractory coating 200 further includes at least one of expanded graphite, expanded vermiculite, sepiolite, and montmorillonite. Expanded graphite, expanded vermiculite, sepiolite, and montmorillonite expand at high temperatures, which can reduce the risk of heat transfer to the substrate 100, thereby improving the fire resistance and heat insulation performance of the refractory coating 200.
[0062] In any embodiment, the refractory coating 200 further includes fillers, including at least one selected from titanium dioxide, carbon black, phthalocyanine blue, and hollow microspheres. Titanium dioxide, carbon black, and phthalocyanine blue are important coloring pigments that can efficiently change the color of the refractory coating 200. The interior of the hollow microspheres is a cavity, and the gas inside the cavity has a low thermal conductivity, which can effectively block the heat conduction path. Applying it to the refractory coating 200 can reduce the thermal conductivity of the refractory coating 200.
[0063] In any embodiment, the thermal conductivity of the refractory coating 200 before expansion is 0.2 W / (m·K) to 0.4 W / (m·K). By adjusting the thermal conductivity of the refractory coating 200 before expansion to the above range, the refractory coating 200 can prevent the rapid spread of heat even in the unexpanded state, thereby achieving effective fire resistance and heat insulation effects even before expansion. The thermal conductivity of the refractory coating 200 before expansion is 0.2 W / (m·K), 0.25 W / (m·K), 0.3 W / (m·K), 0.36 W / (m·K), 0.4 W / (m·K), etc., or a range of any two of the above values, such as 0.2 W / (m·K)~0.25 W / (m·K), 0.25 W / (m·K)~0.3 W / (m·K), 0.3 W / (m·K)~0.36 W / (m·K), 0.36 W / (m·K)~0.4 W / (m·K), etc.
[0064] In any implementation, please refer to Figure 3 , Figure 3 This is another structural schematic diagram of the enclosure panel 1000 provided in this application embodiment, in which a rock wool board 400 is further disposed between the fire-resistant coating 200 and the substrate 100. By providing the rock wool board 400, the thermal insulation performance of the enclosure panel 1000 can be further improved. The rock wool board 400 can not only effectively reduce heat transfer, but also play a role in buffering and delaying the spread of fire in the event of a fire, thereby protecting the substrate 100 from damage by high temperature. This structural design makes the enclosure panel 1000 more stable and safe in high-temperature environments. The rock wool board 400 serves as the bottom thermal insulation barrier, and the fire-resistant coating 200 serves as the surface flame-retardant barrier, forming a dual protection of "physical thermal insulation and chemical flame retardancy", thereby effectively improving the fire resistance and thermal insulation effect of the enclosure panel 1000.
[0065] In any embodiment, the thickness of the rock wool board 400 is less than or equal to 20 mm. By adjusting the thickness of the rock wool board 400 to the above range, both the thermal insulation performance and internal volume of the container can be considered. A rock wool board 400 with a thickness of less than or equal to 20 mm has a smaller impact on the internal space volume of the container, and consequently, a smaller impact on the energy density of the batteries within the container. Specifically, the thickness of the rock wool board 400 can be 5 mm, 10 mm, 15 mm, 20 mm, or any range of two of the above values, such as 5 mm to 10 mm, 10 mm to 15 mm, 15 mm to 20 mm, etc.
[0066] In any embodiment, the thickness of the substrate 100 is 1 mm to 3 mm. By adjusting the thickness of the substrate 100 to the above range, both the mechanical properties and cost of the substrate 100 can be balanced. The thickness of the substrate 100 may be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, or any range of two of the above values, such as 1 mm to 1.5 mm, 1.5 mm to 2 mm, 2 mm to 2.5 mm, 2.5 mm to 3 mm, etc.
[0067] In any embodiment, the substrate 100 includes a metal substrate. The metal substrate maintains high strength at high temperatures, enabling the container to maintain its overall structural integrity during a fire. Furthermore, the high thermal conductivity of the metal substrate rapidly dissipates heat, preventing localized overheating and delaying flame penetration time, thereby increasing the container's fire resistance.
[0068] In any embodiment, the metal substrate includes at least one of aluminum alloy, galvanized steel, stainless steel, carbon steel, and cold-formed thin-walled steel. The aforementioned types of metal substrates can maintain high strength at high temperatures, enabling the container to maintain the integrity of its overall structure during a fire.
[0069] A second aspect of this application provides an energy storage system including the aforementioned battery container. In embodiments of this application, the energy storage system possesses at least the same advantages as the battery container of the first aspect.
[0070] The beneficial effects of this application are further illustrated below with reference to the embodiments.
[0071] To make the technical problems, technical solutions, and beneficial effects solved by the embodiments of this application clearer, the following will provide a more detailed description in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0072] Example 1
[0073] A battery container includes a body panel, which comprises a base plate, a thermal insulation coating, and a fire-resistant coating. The thermal insulation coating is disposed on the side of the base plate away from the receiving cavity, and the fire-resistant coating is disposed on the side opposite to the thermal insulation coating, facing the receiving cavity. The base plate is made of carbon steel and has a thickness of 2 mm. The composition, proportions, thickness, hemispherical emissivity (200 μm–3 mm), and thermal conductivity of the thermal insulation coating, as well as the composition, proportions, thickness, and thermal conductivity before expansion of the fire-resistant coating, are shown in Table 1.
[0074] Example 2
[0075] The difference between Example 2 and Example 1 is that the components of the thermal insulation coating and the proportions of each component are different, as shown in Table 1.
[0076] Examples 3 and 4
[0077] The difference between Examples 3, 4 and 2 is that the thickness of the thermal insulation coating and the fire-resistant coating are different, as shown in Table 1.
[0078] Example 5
[0079] The difference between Example 6 and Example 2 is that a rock wool board with a thickness of 5mm is provided between the refractory coating and the substrate.
[0080] Example 6
[0081] The difference between Example 6 and Example 5 is that the thickness of the rock wool board is different.
[0082] Comparative Example 1
[0083] The difference between Comparative Example 1 and Example 1 is that the structure of the battery container in Comparative Example 1 is different from that in Example 1.
[0084] In Comparative Example 1, the battery container includes a container panel that forms a cavity. The container panel includes a base plate and a rock wool board, with the rock wool board positioned near the cavity. The base plate is made of carbon steel and has a thickness of 2 mm, while the rock wool board has a thickness of 40 mm.
[0085] The specific testing methods for the relevant parameters are as follows:
[0086] 1) Thermal insulation performance test.
[0087] The test shall be conducted in accordance with the test method in Appendix B of GB / T 25261.
[0088] 2) Fire resistance test.
[0089] The test was conducted in accordance with standard EN 1363-1. The specific test procedure is as follows:
[0090] The box panel was placed in the furnace for a fire test, which lasted for 2 hours.
[0091] Place the frame holding the cotton pad against the fire-resistant coated surface of the enclosure panel for up to 30 seconds, or until the cotton pad ignites (defined as glowing or burning). The cotton pad should be applied to all surfaces with the fire-resistant coating, including areas where flames or hot gas from discontinuities, cracks, or gaps are present. During measurement, ensure there is at least a 30 mm gap between the cotton pad facing the enclosure panel and the panel surface parallel to it. There should also be at least a 10 mm gap between the perimeter of the cotton pad and any part of the enclosure panel. The cotton pad holder is provided with protrusions to maintain proper separation from the enclosure panel. Minor adjustments to the position may be made to achieve maximum effect from flames or hot gas. The operator may perform tests to assess the integrity of the enclosure panel. This screening may involve selectively applying cotton pads for short periods to potentially faulty areas and / or moving individual cotton pads over and around these areas. Carbonization of the cotton pad may indicate an impending failure, but a new cotton pad should be used as specified to confirm an integrity failure. Once the cotton pad glows or burns, it should be removed immediately. Any charring or burning of the cotton pad without combustion or light should be disregarded. After use, do not shake the cotton pad or blow air across its surface, as this will prevent the pad from igniting if it should not have been. Ignition time and location should be recorded.
[0092] When using a gap probe, the size of the opening on the enclosure panel surface should be evaluated at intervals determined according to the apparent degradation rate of the enclosure panel. Two gap probes should be used sequentially to determine the size without applying excessive force.
[0093] Can a 6mm slit probe pass through the sample and extend into the furnace, and move 150mm along the gap? Or can a 25mm slit probe pass through the sample and extend into the furnace?
[0094] When using a gap probe, do not forcefully insert it into the gap or pass it horizontally through the gap. Any small gaps in the instrument channel should not be considered, as these have little effect on the transmission of heat through the opening; for example, small gaps caused by deformation of small fasteners in construction joints. The time and location of inserting the gap probe into any opening of the specimen in the prescribed manner should be recorded. (Cotton pad requirements: Unless it is a special standard in a special component, the cotton pad used for integrity measurement should consist of 100% new, untreated, undyed soft cotton fibers, weighing between 3g and 4g per 100mm × 100mm × 20mm. Before use, it should be dried in an oven at (100±5)℃ for at least 30 minutes. After drying, it can be stored in a desiccator or sealed container for up to one week, and then oven dried again as described above. When using, it should be mounted on a handle with dimensions of (100±5)mm × (100±5)mm × (20±1)mm.)
[0095] Slit probe requirements: Two types of slit probes shall be provided for measuring integrity, and they shall be made of cylindrical steel rods with diameters of (6±0.1) mm and (25±0.2) mm. They shall be equipped with insulated handles of appropriate length. Unless otherwise specified in the relevant test methods, the integrity of the separation element shall be assessed throughout the test by using cotton pads, probes, and monitoring for evidence of continued burning of the specimen.
[0096] After 2 hours of testing, the integrity and thermal insulation performance of the enclosure panels were tested.
[0097] Integrity tests include: a test to see if the cotton pad can be ignited and a test to see if a gap probe can pass through.
[0098] The thermal insulation performance test includes measuring the average temperature rise on the side of the enclosure panel away from the fire-resistant coating and the highest temperature rise at any point on the side of the enclosure panel away from the fire-resistant coating.
[0099] 3) Adhesion test.
[0100] The test was conducted in accordance with the GB / T 5210 standard.
[0101] 4) Abrasion resistance test.
[0102] The test was conducted in accordance with the GB / T 1768 standard, using a CS-17 grinding wheel with a load of 1 kg.
[0103] 5) Stone impact resistance test.
[0104] The test was conducted in accordance with ISO 20567-1-2017 standard, using a VDA series spray gun, 1mm to 2mm prismatic quartz sand, 1kg gravel weight, an impact pressure of 0.5*1.5 bar, an impact time of 10s, an impact angle of 54°, and 15 impact cycles.
[0105] 6) Thermal conductivity test.
[0106] The transient plane method was used for testing, referencing the testing standard ISO22007-2. Samples with a diameter and thickness of 30mm x 2mm were prepared using a mold and tested using a C-Therm TH-91-13-00654 thermal conductivity meter from Canada.
[0107] 7) Hemispherical emissivity test.
[0108] The test standard for hemispherical emissivity is GB / T 25261.
[0109] 8) Particle size test of hollow microspheres.
[0110] Take a cross-section of the thermal insulation coating or scrape off powder from the thermal insulation coating, and use an electron microscope or optical microscope to measure the particle size of the hollow microspheres in the cross-section or powder.
[0111] 9) Pore size test of hollow microspheres.
[0112] Take a cross-section of the thermal insulation coating and use an electron microscope or optical microscope to measure the pore size of the hollow microspheres in the cross-section.
[0113] The above are merely embodiments of this application and do not limit the scope of this patent application. Any equivalent structural or procedural changes made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of this application.
[0114]
[0115]
[0116] 1) In Examples 1 to 6, the thickness of the thermal insulation coating ranges from 200 μm to 3 mm, and the thermal insulation temperature difference ranges from 10.5℃ to 34.8℃. In Comparative Example 1, the thickness of the rock wool board is 40 mm, and the thermal insulation temperature difference is 6.6℃. It can be seen that, compared to Comparative Example 1, Examples 1 to 6, while maintaining their thermal insulation performance, can increase the internal space volume of the container, thereby increasing the energy density of the battery within the container.
[0117] 2) Compared with Example 1, the container prepared in Example 2 has better thermal insulation performance. This is because silica aerogel is added to the thermal insulation coating in Example 2. Silica aerogel has a porous structure, and the movement of gas molecules in the pores is restricted, which can greatly reduce heat conduction and reduce the thermal conductivity of the thermal insulation coating, thereby improving the thermal insulation effect of the thermal insulation coating.
[0118] 3) The data from Examples 2 to 4 show that increasing the thickness of the thermal insulation coating within a certain range can improve the thermal insulation effect of the thermal insulation coating, and increasing the thickness of the refractory coating within a certain range can improve the refractory performance of the refractory coating.
[0119] 4) The data from Examples 5 and 6 show that placing a rock wool board of a certain thickness between the fire-resistant coating and the substrate can further improve the fire resistance of the container to a certain extent.
[0120] 5) In Examples 1 to 6, the thermal insulation coating contains acrylic acid. Because acrylic acid has good adhesion, its application in the thermal insulation coating ensures good adhesion to the substrate. The thermal insulation coating also contains hollow microspheres and aerogel. The hollow structure of the microspheres deforms under external forces (such as friction or impact), effectively absorbing and dispersing stress, reducing local stress concentration, and improving the wear resistance and stone impact resistance of the thermal insulation coating. The porous structure of the aerogel allows it to absorb a large amount of energy through pore compression when impacted, significantly buffering the destructive force of high-speed impacts such as stone impacts, thus improving the stone impact resistance of the thermal insulation coating.
[0121] 6) In Examples 1 to 6, the refractory coating contains epoxy resin and polyetheramine. The above materials are two-component cross-linking curing materials. Some components of the two-component cross-linking curing materials contain polar groups. These polar groups can form chemical bonds with the oxides or treatment layers on the substrate surface, thereby enhancing the interfacial bonding force and enabling the refractory coating to have good adhesion on the substrate.
[0122] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A container for batteries, characterized in that, The battery container includes a container panel that surrounds a cavity. The container panel includes a base plate, a thermal insulation coating, and a fire-resistant coating. The thermal insulation coating is disposed on the side of the base plate away from the cavity, and the fire-resistant coating is disposed on the side opposite to the thermal insulation coating, with the fire-resistant coating facing the cavity.
2. The battery container according to claim 1, characterized in that, The thickness of the thermal insulation coating is 200μm~3mm.
3. The battery container according to claim 1 or 2, characterized in that, The thermal insulation coating has an emissivity of 85% to 99% in a hemispherical region of 200 μm to 3 mm.
4. The battery container according to claim 1 or 2, characterized in that, The thermal conductivity of the insulation coating is 0.002 W / (m·K) to 0.05 W / (m·K).
5. The battery container according to claim 1 or 2, characterized in that, The thermal insulation coating includes at least one of acrylic, polyurethane, fluorocarbon, and silicone.
6. The battery container according to claim 1 or 2, characterized in that, The thermal insulation coating also includes hollow microspheres; Optionally, the particle size of the hollow microspheres is 1 μm to 100 μm; Optionally, the pore size of the hollow microspheres is 0.5 μm to 90 μm; Optionally, the hollow microspheres include at least one of hollow ceramic microspheres, hollow alumina microspheres, hollow carbon microspheres, hollow polystyrene microspheres, and hollow polyimide microspheres.
7. The battery container according to claim 1 or 2, characterized in that, The thermal insulation coating also includes aerogel; Optionally, the aerogel includes at least one of silica aerogel, carbon aerogel, alumina aerogel, zirconia aerogel, polymethyl methacrylate aerogel, and polyimide aerogel.
8. The battery container according to claim 1 or 2, characterized in that, The thickness of the refractory coating is 1.5mm to 20mm.
9. The battery container according to claim 1 or 2, characterized in that, The refractory coating comprises at least one of the following: a copolymer of epoxy and amine materials, a copolymer of hydroxyl polyurethane and isocyanate, a copolymer of acrylic acid and isocyanate, and polyurea.
10. The battery container according to claim 9, characterized in that, The refractory coating also includes at least one of the following: ammonium phosphate compounds and their polymers, amine compounds and their derivatives, and polyol polymers.
11. The battery container according to claim 1 or 2, characterized in that, The thermal conductivity of the refractory coating before expansion is 0.2 W / (m·K) to 0.4 W / (m·K).
12. The battery container according to claim 1 or 2, characterized in that, A rock wool board is further disposed between the fire-resistant coating and the substrate; optionally, the thickness of the rock wool board is less than or equal to 20 mm.
13. The battery container according to claim 1 or 2, characterized in that, The thickness of the substrate is 1mm to 3mm.
14. The battery container according to claim 1 or 2, characterized in that, The substrate includes a metal substrate; Optionally, the metal substrate includes at least one of aluminum alloy, galvanized steel, stainless steel, carbon steel, and cold-formed thin-walled steel.
15. An energy storage system, characterized in that, This includes battery containers as described in any one of claims 1-14.